Andy Warhol, 365 takes the Andy Warhol Museum collection (Abrams, 2004)
Andy Warhol was a notorious collector who saved practically everything that came his way. In 1994, seven years after the artist's death, The Andy Warhol Museum in Pittsburgh became the repository not only for a substantial body of his artwork and films, but also for the Time Capsules into which he obsessively deposited a lifetime's worth of ephemera and personal memorabilia. For this book, the museum has gathered highlights of its collection. Illustrated with almost 400 objects, from paintings to party invitations, the volume also features lively commentaries by the museum's staff as well as quotes from Warhol's own irreverent writings.